Partida de motores de indução com limitação supercondutora : estudo conceitual e por simulação - Urtubi, Ismael de La Varga (2009)
This paper presents a study on limiting the starting current of three-phase squirrel-cage induction motors by using superconducting materials that, under certain conditions, have no resistance to the passage of electric current. The superconducting material must be immersed in liquid nitrogen to achieve a cooling of 77K (-195.6°C). At this temperature it has no electrical resistance. Also it is known that superconductivity is destroyed when it exceeds any of three elements: critical temperature (Tc), critical current density (Jc) or critical magnetic field (Hc). In our study we relate the critical current density (Jc) with the critical current (Ic), with which we work, because when exceeded, the electrical resistance of the material is no longer zero. Therefore, to limit the starting current it will be inserted a superconductor between the power supply and the stator of the induction motor. The starting current is very high exceeding the critical current (Ic) of the superconductor. At that moment, the superconductor behaves as a conductor and a resistance is inserted in the circuit causing an immediate reduction in the starting current. When the current falls below the critical current (Ic), it again becomes a superconductor removing the resistance of the circuit. A superconductor behavior is also presented for the motor operating at steady state. It is presented a methodology to design the values of resistance and critical current of superconducting limiter. Simulation results shows the validity of the method, and the feasibility of limiting the starting current of three phase induction motor with this technology.